Assessment of a Dietary Consultation Model for Effective Diabetes Care in Saudi Population using Partial Least Squares Estimation - Sami, Waqas; Ansari, Tahir; Butt, Nadeem Shafique; Mohd Rashid, Ab Hamid (PJSOR, 2018)
The relationship between dietary habits and diabetes has not been studied efficiently in Saudi Arabia and the available diabetes risk models does not focus much on diet, nor do they capture the overall dietary behaviors. The purpose of this research was to test empirically the hypothesised dietary consultation model that has been proposed for more effective diabetes care. This exploratory study was conducted on type 2 diabetic Saudi patients visiting the Primary Health Care Centres in Almajmaah city. The data comprising 350 patients were collected from 5th February – 24th April, 2017 through systematic sampling technique using direct investigation method. Data was collected through four questionnaires. Composite scores were extracted for all variables under study and analysed by Partial Least Squares-Structural Equation Modelling approach using SmartPLS 3.2.6 software. Evaluation of formative outer and inner model relationships validated the hypothesised dietary consultation model. Power of study, coefficient of determination, effect size, total effects, and model fit index further validated the findings. The validated dietary consultation model facilitates a new healthcare paradigm which can give a better understanding of diabetes management at stakeholder and individual level. Healthcare givers should pay special emphasis on diabetics’ diabetes mellitus knowledge, dietary knowledge, and dietary attitude, as these factors influence each other, dietary practices and HbA1c. Healthcare givers can use this model alone or by integrating it with available diabetes risk models to carry out the dietary assessment of type 2 diabetics.